First-principles study of electronic properties of Cu doped Ag2S. (1st October 2018) - Du, Chunyan; Zhao, Yangyang; Liu, Xiaojie; Shan, Guiye
Abstract: Using first-principles calculations based on density functional theory, electronic properties of Ag2 S and Cu doped Ag2 S were investigated. The calculated results show that Ag2 S crystal is semiconductor with a band gap of 0.92 eV which is consistent with previous PBE calculation. Three possible Cu doping configurations are investigated: Cu substitution of Ag_I, Cu substitution of Ag_II, and interstitial Cu. It is found that interstitial Cu doping reduces the band gap as the Cu concentration increases, while for Ag_I and Ag_II substitution doping the band gap is not sensitive to the impurity concentration. The band gap reduction can mainly be attributed to the downward shift of the bottom of conduction band upon Cu interstitial doping. The reduction of the band gap for Ag2 S with interstitial Cu doping is consistent with experimental absorption and fluorescence spectra, where a significant red-shift after Cu doping in Ag2 S crystal is observed.